The Effect of Training in the Preparatory and Competitive Periods on Trunk Rotational Power in Canoeists, Ice-Hockey Players, and Tennis Players - Oliver Poór; Erika Zemková (MDPI AG, 2018)
This study evaluates changes in trunk rotational power at different weights and velocities after the preparatory and competitive periods in ice-hockey players, tennis players, and canoeists. The subjects performed trunk rotations to each side with a barbell of different weights placed on the shoulders (6, 10, 12, 16, 20, 22, and 26 kg) prior to and after 6 weeks of the preparatory period and 6 weeks of the competitive period. The results showed that mean power produced in the acceleration phase of trunk rotations increased significantly at weights from 10 to 26 kg or 6 to 26 kg after the preparatory and competitive periods in tennis players. The values obtained during trunk rotations with weights ≥12 kg also increased significantly after the preparatory period in ice-hockey players, whereas there were no significant changes after the competitive period. Similarly, the mean power during trunk rotations with weights ≥10 kg increased significantly only after the preparatory period in canoeists. Similar changes were observed for the peak power. These findings demonstrate that changes in trunk rotational power reflect the specificity of their training programs. This information may provide a basis for designing exercises focused on improvements of power produced during trunk rotations under loading conditions.